Creativity in large-scale contexts : [guiding creative engagement and exploration] - Feinstein, Jonathan S., 1960- (Stanford, California : Stanford Business Books, an imprint of Stanford University Press, 2023)
"Innovators and creators work in cultural and environmental contexts that shape their work. These contexts are large scale, filled with multitudes of elements and possibilities. Creativity in Large-Scale Contexts, by Yale Professor Jonathan Feinstein, introduces a groundbreaking new network model to describe how successful creativity is generated in such contexts. The book will help groups and organizations be more productive and efficient in their innovation work. Feinstein argues that in large-scale contexts creativity happens most efficiently when it is actively "guided." Guiding creativity involves understanding and navigating the creative context, imagining new ways to use it, identifying puzzles and opportunities, and spanning these to create novel connections. With thoughtful guidance, creators and creative teams can find their way through the thicket of possibilities faster, smarter, and with less waste. Feinstein describes two forms of guidance--guiding conceptions and guiding principles--and shows how they work together to generate creativity. Creativity in Large-Scale Contexts draws on case studies of famous creators including Virginia Woolf, Albert Einstein, Indigenous artist Clifford Possum, transgender activist and engineer Lynn Conway, and Twitter cofounder Jack Dorsey. Empirically grounded, this book will be essential for teaching and managing creativity and innovation and will open new avenues for future intellectual growth in the field"--
Context. The importance of context ; The structure of context ; Examples of context ; Modeling context ; Ideas and projects -- Guidance. The challenge of creativity ; Guiding conceptions introduced ; Examples of guiding conceptions ; Guiding conceptions in greater depth ; The model of guiding conceptions and the benefits of guided search ; Guiding principles introduced ; Examples of guiding principles ; Modeling guiding principles and how they function in tandem with guiding conceptions -- Creation. A core model of creativity ; Creative journeys ; Modeling richer creative processes ; The creative development of fields ; Supporting creativity -- Conclusion : the path forward.
Subtitle from cover image on De Gruyter resource palge.
Includes bibliographical references and index.
Description based on online resource; title from digital title page (De Gruyter, viewed May 3, 2024).
eBooks on EBSCOhost
Keywords: Creative ability; Créativité.; creativity; PSYCHOLOGY / Creative Ability; Creative ability